SOCIETY AWARENESS AS A STRATEGY FOR CONSERVATION OF NATURAL RESOURCES - Sengwar, Babita (International Journal of Research -GRANTHAALAYAH, 2015)
Conservation is the proper management of natural resources to prevent its exploitation, destruction or degradation. India is blessed with natural resources but these resources from our research study on the usage of natural resources are depleting every day. As we know nature provides all the basic needs which are necessary to us but we are over exploiting or over using these resources. Conservation of natural resources has acquired great attention at present. It is high time that man must realize of the grave consequences of his action which are damaging the environment beyond repair. If we continue exploit the nature, there will be no more natural resources available in the future. So, there is an urgent need to conserve the nature for future. Society participation in the conservation of natural resources is vital importance so we must get them involved in this national task. A society, a state, a country, the whole world is a collection of individuals in a final analysis. Therefore, if individual does his or her duty to perfection, the whole world can become less pollution free and we can conserve our natural resources. It is the duty of us to spread awareness among the society in this regard.